2017
DOI: 10.1038/s41598-017-00972-5
|View full text |Cite
|
Sign up to set email alerts
|

Pestalotiopsis and allied genera from Camellia, with description of 11 new species from China

Abstract: A total of 124 Pestalotiopsis-like isolates associated with symptomatic and asymptomatic tissues of Camellia sinensis and other Camellia spp. from eight provinces in China were investigated. Based on single-and multi-locus (ITS, TEF, TUB2) phylogenies, as well as morphological characters, host associations and geographical distributions, they were classified into at least 19 species in three genera, i.e. Neopestalotiopsis, Pestalotiopsis and Pseudopestalotiopsis. Eight novel species in Pestalotiopsis and three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 32 publications
(45 reference statements)
5
56
0
Order By: Relevance
“…The alignment contained 1500 characters (521 for ITS, 483 for TUB, and 496 for TEF) and the combined datasets resulted in a best scoring RAxML tree with a final maximum likelihood (ML) optimization value of likelihood of −6532.281881, shown in Figure 4 . The overall topology of our tree is comparable to that of earlier studies [ 17 , 20 , 32 ]. However, the overall branch-length support values were lower in most clades and recent studies have shown that the use of combined ITS, TEF, and TUB sequences to resolve numbers of cryptic species in pestalotiopsis-like taxa have some shortcomings.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The alignment contained 1500 characters (521 for ITS, 483 for TUB, and 496 for TEF) and the combined datasets resulted in a best scoring RAxML tree with a final maximum likelihood (ML) optimization value of likelihood of −6532.281881, shown in Figure 4 . The overall topology of our tree is comparable to that of earlier studies [ 17 , 20 , 32 ]. However, the overall branch-length support values were lower in most clades and recent studies have shown that the use of combined ITS, TEF, and TUB sequences to resolve numbers of cryptic species in pestalotiopsis-like taxa have some shortcomings.…”
Section: Resultssupporting
confidence: 84%
“…The overall topology of our phylogenetic tree was not sufficiently supported, similar to that published in previous studies that maintained the Neopestalotiopsis isolates as Neopestalotiopsis spp. [ 17 , 32 , 33 , 34 , 35 ]. Although multi-locus phylogeny is important in species differentiation, there is still a lack of species deposited in public culture collections and only a fraction of DNA has been sequenced [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Phenotypically cryptic speciation and convergent evolution are frequent in fungi (Crespo and Pérez-Ortega 2009;Cai et al 2011;Moncada et al 2014;Balasundaram et al 2015;Jayawardena et al 2016;Liu et al 2017;Kruse et al 2018b). Formal taxonomy that recognizes cryptic species may appear impractical because the molecular tools necessary for precise identification are out of reach for many users.…”
Section: Challenges With Regard To Unambiguous Identification Of Fungimentioning
confidence: 99%
“…Likewise, Pseudopestalotiopsis was distinguished from Pestalotiopsis by generally dark coloured concolourous median cells with indistinct conidiophores. However, Liu et al (2017) found that there were exceptions, and that some taxa clustering within Neopestalotiopsis produced concolourous median cells, suggesting that conidial pigmentation is more plastic among these genera than originally proposed by Maharachchikumbura et al (2014).…”
Section: Dinemasporium/stauronema and Pseudolachnea/ Pseudolachnellamentioning
confidence: 79%